Effects of Guide Vane Inclination in Axial Shelling Unit on Corn Shelling Performance - Saeng-ong, Phatchanida; Chuan-Udom, Somchai; Saengprachatanarak, Khwantri (Agriculture and Natural Resources, 2015)
This study was conducted on the effects of guide vane inclination of an axial shelling unit on corn shelling performance, based on loss from the shelling unit, grain breakage, power requirements and specific energy consumption. It was found that when the guide vane inclination increased, loss from the shelling unit had a tendency to decrease, the power requirements and specific energy consumption tended to increase linearly and the grain breakage difference was not significant. A study of the rotor speed and feed rate showed that an increased rotor speed could decrease the loss from shelling, while the grain breakage, power requirements and specific energy consumption tended to increase. Increasing the feed rate increased the loss from the shelling unit, grain breakage and power requirements; additionally, it decreased the specific energy consumption.